Efektivitas Model Lesson Study dalam Penerapan Pembelajaran Konstruktivisme pada SMA/MA Di Kabupaten Kutai Barat Provinsi Kalimantan Timur Tahun 2012 - Zeni Haryanto (Media Komunikasi FPIPS, 2013)
Based on the mapping of the standard competence/basic competence of students in     each subject is mainly targeted at schools in West Kutai regency into the sample     obtained by the fact that over 50% of the standard of competence in each subject     cannot be reach by the UN students. It is necessary for improvement in the standard     of the learning process to conduct training on constructivist learning for teachers of     each subject and implemented through the lesson study model. The model consists     of lesson study phase of Plan, Do and See. The results of the learning observations     is then discussed in the reflection on the stage See to know what needs to be     improved in the teaching and learning activities of students at the time. Based on     the analysis of the instrument can be concluded that a guide of the lesson study     model is produced that can be applied to implement school-based lesson study in     West Kutai District with the effectiveness of the implementation by 91%, or can be     said to be very effective.      Keywords: Effectiveness, Lesson Study Model, Learning,  Constructivism